Regional network covariance patterns of white matter integrity related to cardiorespiratory fitness in healthy aging - Samantha G. Smith; Samantha G. Smith; Pradyumna K. Bharadwaj; Pradyumna K. Bharadwaj; David A. Raichlen; David A. Raichlen; Matthew D. Grilli; Matthew D. Grilli; Matthew D. Grilli; Jessica R. Andrews-Hanna; Jessica R. Andrews-Hanna; Georg A. Hishaw; et al. (Frontiers in Aging Neuroscience, 2025)
Cardiorespiratory fitness (CRF), measured by VO2max, is an indicator of vascular functioning that can influence the integrity of brain microstructural white matter tracts in aging. How CRF is related to regional patterns of white matter bundles for magnetic resonance imaging (MRI) diffusion metrics (axial diffusivity, AD; radial diffusivity, RD; mean diffusivity, MD; fractional anisotropy, FA) has been less studied. We used a multivariate analysis method, the Scaled Subprofile Model (SSM), to identify network patterns of MRI tract-specific white matter integrity (WMI) for AD, RD, MD, and FA related to VO2max and to evaluate their relation to demographic, vascular health, and dementia risk factors in 167 cognitively unimpaired older adults, ages 50 to 88. We identified four CRF-related regional patterns of WMI characterized by enhanced integrity in commissural pathways that connect areas within anterior brain regions (prefrontal body of the corpus callosum), connect subcortical regions to one another (fornix), and include selected association tracts (arcuate fasciculus, superior longitudinal fasciculus). Greater white matter lesion load, in addition to age, was associated with reduced expression of all four CRF-WMI patterns, while high vascular risk level was further associated with reduced expression of the RD, MD, and FA patterns. The regional patterns of RD and FA were most strongly associated with CRF. The results suggest that in healthy older adults, enhanced CRF is differentially associated with regional patterns of WMI, which are related to age and further impacted by macrostructural white matter lesion load and vascular risk. These findings support the use of the multivariate SSM in identifying regional patterns of white matter tracts that may provide markers of brain aging and cerebrovascular health.